Pengaruh lingkungan kerja fisik dan lingkungan kerja non fisik terhadap tindakan keselamatan dan kesehatan kerja (K3) di PT. Mitra Bumi - Vivi Indriani; Yusni Ikhwan Siregar; Syahril Syahril (Pelantar Press, 2021)
Occupational Safety and Health (OSH) is one of the protection measures aimed at all potentials that can cause danger, so that workers and other people in the workplace are always safe and healthy and all production sources can be used safely and efficiently. The purpose of this study is to determine the relationship between physical work environment (lighting, temperature, noise and humidity) and non-physical (knowledge of workers, behavior based safety, availability of tools and company regulations) to occupational safety and health (OSH) measures and to determine the most important factors. dominant in the physical work environment and non-physical work environment to the Occupational Safety and Health (OSH) action at PT. Mitra Bumi. This research was conducted at PT. Mitra Bumi in January-March 2020. This type of research is a quantitative study with a cross sectional study approach. The results showed that there is a relationship between the physical work environment (lighting, temperature, noise and humidity) to the Occupational Health and Safety (OSH) measures at PT. Mitra Bumi. There is no relationship between the non-physical work environment (workers' knowledge, behavior based safety, availability of company tools and regulations) to Occupational Safety and Health (OSH) actions at PT. Mitra Bumi. The most dominant factor on the action of Occupational Safety and Health (OSH) at PT. Mitra Bumi is a physical work environment, namely lighting and noise.